Cell Painting phenomics reveals size-dependent phenotypic responses to titanium dioxide nanoparticles in HepG2 cells - Adil Boustani; Abir Ounoughi; Jonas Zetzsche; Patrik Karlsson; Oleksandr Kotlyar; Eva Särndahl; Magnus Engwall; Nikolai Scherbak; Andi Alijagic (Toxicology, 2026)

Effect-based spatiotemporal assessment of suspended particulate matter in the River Rhine: An early warning platform for environmental monitoring - Erica Selin; Fredric Södergren Seilitz; Javad Mottaghipisheh; Geeta Mandava; Johan Lundqvist; Anna Kärrman; Magnus Engwall; Lutz Ahrens; Dirk Repsilber; Oleksandr Kotlyar; Andi Alijagic; Jan Koschorreck; et al. (Journal of Hazardous Materials, 2026)

Virtual effect-directed analysis of granulated rubber identifies bioactive chemicals and distinct hazard profiles - Fredric Södergren Seilitz; Ayan Au Musse; Nathalie Struwe; Andi Alijagic; Anna Kärrman; Arslan Hashmi; Thanh Wang; Magnus Engwall; Maria Larsson (Journal of Hazardous Materials, 2026)

Nanoplastics drive toxicity under co-exposure with perfluorooctanesulfonic acid in human intestinal cells - Andi Alijagic; Eva Särndahl; Oleksandr Kotlyar; Patrik Karlsson; Daniel Duberg; Nikolai Scherbak; Annalisa Pinsino; Magnus Engwall; Tuulia Hyötyläinen (Environmental Chemistry Letters, 2025)
Per- and polyfluoroalkyl substances and nanoplastics frequently co-occur in environmental matrices, yet the effects of co-exposure on cellular responses upon ingestion are poorly understood. Here, we exposed human intestinal Caco-2 cells to perfluorooctanesulfonic acid, nanoplastics, and their combination. Cell painting-based phenomics was used to map phenotypic alterations across subcellular structures, and untargeted metabolomics using ultra-high-performance liquid chromatography coupled to quadrupole time-of-flight mass spectrometry was employed to assess metabolic changes. Results show that perfluorooctanesulfonic acid predominantly affected the actin cytoskeleton, Golgi apparatus, and plasma membrane, while nanoplastics primarily targeted mitochondria. Combined exposure disrupted the endoplasmic reticulum, RNA, and mitochondria. Perfluorooctanesulfonic acid reduced levels of carnitines, free fatty acids, nucleotides, and sugars, whereas nanoplastics inhibited ceramides, triglycerides, sphingomyelins, and additional free fatty acids. Combined exposure produced a metabolic profile resembling that of nanoplastics, with specific differences attributed to perfluorooctanesulfonic acid. Overall, nanoplastics appear as the main drivers of the co-exposure effects.

Sea urchin immune cells and associated microbiota co-exposed to iron oxide nanoparticles activate cellular and molecular reprogramming that promotes physiological adaptation - Andi Alijagic; Roberta Russo; Viviana Scuderi; Martina Ussia; Silvia Scalese; Simona Taverna; Magnus Engwall; Annalisa Pinsino (Journal of Hazardous Materials, 2025)

Deciphering the phenotypic, inflammatory, and endocrine disrupting impacts of e-waste plastic-associated chemicals - Andi Alijagic; Fredric Södergren Seilitz; Anna Bredberg; Aron Hakonen; Maria Larsson; Erica Selin; Viktor Sjöberg; Oleksandr Kotlyar; Nikolai Scherbak; Dirk Repsilber; Anna Kärrman; Thanh Wang; et al. (Environmental Research, 2025)

Cocktail effects of tire wear particles leachates on diverse biological models: A multilevel analysis - Jessy Le Du-Carrée; Clara Kempkens Palacios; Anna Rotander; Maria Larsson; Andi Alijagic; Oleksandr Kotlyar; Magnus Engwall; Viktor Sjöberg; Steffen H. Keiter; Rodrigo Almeda (Journal of Hazardous Materials, 2024)

Results of an international interlaboratory study on dioxin-like activities in drinking-, river surface- and wastewater using DR CALUX bioassay - Peter Behnisch; Harrie Besselink; Go Suzuki; Sebastian Buchinger; Georg Reifferscheid; Marcus Lukas; Marc Wollenweber; Simone Wollenweber; Henner Hollert; Tatsuya Kunisue; Nguyen Minh Tue; Andi Alijagic; et al. (Science of The Total Environment, 2024)

Aryl hydrocarbon receptor-mediated potencies in field-deployed plastics vary by type of polymer - Christine Schönlau; Maria Larsson; Monika M. Lam; Magnus Engwall; John P. Giesy; Chelsea Rochman; Anna Kärrman (Environmental Science and Pollution Research, 2019)

Effects of perfluorooctane sulfonate on genes controlling hepatic fatty acid metabolism in livers of chicken embryos - Annette V. Jacobsen; Marcus Nordén; Magnus Engwall; Nikolai Scherbak (Environmental Science and Pollution Research, 2018)

Developmental toxicity of PFOS and PFOA in great cormorant (Phalacrocorax carbo sinensis), herring gull (Larus argentatus) and chicken (Gallus gallus domesticus) - Marcus Nordén; Urs Berger; Magnus Engwall (Environmental Science and Pollution Research, 2016)

Investigations on sediment toxicity of German rivers applying a standardized bioassay battery - Christoph Hafner; Stefan Gartiser; Manuel Garcia-Käufer; Sabrina Schiwy; Christoph Hercher; Wiebke Meyer; Christine Achten; Maria Larsson; Magnus Engwall; Steffen Keiter; Henner Hollert (Environmental Science and Pollution Research, 2015)

An oxygenated metabolite of benzo[a]pyrene increases hepatic β-oxidation of fatty acids in chick embryos - Ola Westman; Maria Larsson; Nikolaos Venizelos; Henner Hollert; Magnus Engwall (Environmental Science and Pollution Research, 2014)

Chemical and bioanalytical characterisation of PAHs in risk assessment of remediated PAH-contaminated soils - Maria Larsson; Jessika Hagberg; Anna Rotander; Bert van Bavel; Magnus Engwall (Environmental Science and Pollution Research, 2013)

High levels of perfluoroalkyl acids in eggs and embryo livers of great cormorant (Phalacrocorax carbo sinensis) and herring gull (Larus argentatus) from Lake Vänern, Sweden - Marcus Nordén; Urs Berger; Magnus Engwall (Environmental Science and Pollution Research, 2013)

The dioRAMA project: assessment of dioxin-like activity in sediments and fish (Rutilus rutilus) in support of the ecotoxicological characterization of sediments - Kathrin Eichbaum; Markus Brinkmann; Sebastian Buchinger; Markus Hecker; Magnus Engwall; Bert van Bavel; Georg Reifferscheid; Henner Hollert (Journal of Soils and Sediments, 2013)

Polycyclic aromatic hydrocarbons (PAHs) reduce hepatic β-oxidation of fatty acids in chick embryos - Ola Westman; Marcus Nordén; Maria Larsson; Jessica Johansson; Nikolaos Venizelos; Henner Hollert; Magnus Engwall (Environmental Science and Pollution Research, 2013)

Perfluorooctane sulfonate increases β-oxidation of palmitic acid in chicken liver - Marcus Nordén; Ola Westman; Nikolaos Venizelos; Magnus Engwall (Environmental Science and Pollution Research, 2012)

Some heterocyclic aromatic compounds are Ah receptor agonists in the DR-CALUX assay and the EROD assay with RTL-W1 cells - Gunnar Hinger; Markus Brinkmann; Kerstin Bluhm; Anne Sagner; Helena Takner; Adolf Eisenträger; Thomas Braunbeck; Magnus Engwall; Andreas Tiehm; Henner Hollert (Environmental Science and Pollution Research, 2011)

AhR agonist and genotoxicant bioavailability in a PAH-contaminated soil undergoing biological treatment - Erika Andersson; Anna Rotander; Thomas von Kronhelm; Anna Berggren; Per Ivarsson; Henner Hollert; Magnus Engwall (Environmental Science and Pollution Research, 2009)

Changes in toxicity and Ah receptor agonist activity of suspended particulate matter during flood events at the rivers Neckar and Rhine — a mass balance approach using in vitro methods and chemical analysis - Jan Wölz; Magnus Engwall; Sibylle Maletz; Helena Olsman Takner; Bert van Bavel; Ulrike Kammann; Martin Klempt; Roland Weber; Thomas Braunbeck; Henner Hollert (Environmental Science and Pollution Research, 2008)

Reed beds receiving industrial sludge containing nitroaromatic compounds - Lillemor Gustavsson; Henner Hollert; Sofie Jönsson; Bert van Bavel; Magnus Engwall (Environmental Science and Pollution Research, 2007)

Perfluorooctane Sulfonate Increases the Genotoxicity of Cyclophosphamide in the Micronucleus Assay with V79 Cells: Further Proof of Alterations in Cell Membrane Properties Caused by PFOS (3 pp) - Harald Färber; Paul Jones; John Giesy; Magnus Engwall (Environmental Science and Pollution Research, 2007)

Fractionation and Determination of Ah Receptor (AhR) Agonists in Organic Waste After Anaerobic Biodegradation and in Batch Experiments with PCB and decaBDE (8 pp) - Helena Olsman; Anna Schnürer; Helén Björnfoth; Bert van Bavel; Magnus Engwall (Environmental Science and Pollution Research, 2007)

Ah Receptor Agonists in UV-exposed Toluene Solutions of Decabromodiphenyl Ether (decaBDE) and in Soils Contaminated with Polybrominated Diphenyl Ethers (PBDEs) (9 pp) - Helena Olsman; Jessika Hagberg; Georgi Kalbin; Anneli Julander; Bert van Bavel; Åke Strid; Mats Tysklind; Magnus Engwall (Environmental Science and Pollution Research, 2006)

Fate of ah receptor agonists during biological treatment of an industrial sludge containing explosives and pharmaceutical residues - Lillemor K. Gustavsson; Nina Klee; Helena Olsman; Henner Hollert; Magnus Engwall (Environmental Science and Pollution Research, 2004)

Changes in toxicity and genotoxicity of industrial sewage sludge samples containing nitro- and amino-aromatic compounds following treatment in bioreactors with different oxygen regimes - Nina Klee; Lillemor Gustavsson; Thomas Kosmehl; Magnus Engwall; Lothar Erdinger; Thomas Braunbeck; Henner Hollert (Environmental Science and Pollution Research, 2004)

Biological and Chemical Determination of Dioxin-like Compounds in Sediments by Means of a Sediment Triad Approach in the Catchment Area of the River Neckar - Henner Hollert; Matthias Dürr; Helena Olsman; Krister Halldin; Bert van Bavel; Werner Brack; Mats Tysklind; Magnus Engwall; Thomas Braunbeck (Ecotoxicology, 2002)

Ethoxyresorufin - Magnus Engwall; Björn Brunström; Eva Jakobsson (Archives of Toxicology, 1994)

Ethoxyresorufin O-deethylase (EROD) and aryl hydrocarbon hydroxylase (AHH)-inducing potency and lethality of chlorinated naphthalenes in chicken (Gallus domesticus) and eider duck (Somateria mollissima) embryos - Magnus Engwall; Björn Brunström; Eva Jakobsson (Archives of Toxicology, 1994)